Agency costs and the size discount: evidence from acquisitions - Offenberg, David (2010)
Many scholars have found a negative relationship between a firm’s size and its value, as measured by Tobin’s q. This result is called the size discount. There are hypotheses about why the size discount exists, but none have been rigorously empirically tested. This paper argues that the size discount is created by the inability of shareholders to minimize agency costs in larger companies. Statistical tests suggest that the size discount only appears in large firms with managers that impose excessive agency costs upon their shareholders. Empiricists who use Tobin’s q to proxy for growth opportunities may need a different proxy.